Lateral asymmetries in the kick movement and the soccer and futsal performance - F.A. Barbieri; L.T.B. Gobbi (Desafio Singular, 2009)
For proficiency, on soccer and futsal, is necessary that the athlete has similar performance between contralateral limbs. However, few athletes show this level of behavior. The aim of this study was to review in the literature the side asymmetry on soccer and futsal kick and what its effects on performance. The study used a systematic review to answer the questions. The results showed asymmetries between contralateral limbs with respect to the ability to kick, requiring proper and equality training between the sides to develop similarly limbs. Moreover, the similarity should be at the highest level, in other words, on performance level of the dominant limb. In the training, greater emphasis to aspects of the kick kinematic than the aspects related to the strength should be performed as much the kick limb as the support limb. We conclude that the asymmetries between the sides in the kicks affect the athletes' performance during the game, but this issue is not yet solved, requiring further studies with respect to training and the differences between the sides.